Extraordinary halocarbon emissions initiated by the 2011 Tohoku earthquake. Issue 7 (6th April 2015) - Saito, Takuya; Fang, Xuekun; Stohl, Andreas; Yokouchi, Yoko; Zeng, Jiye; Fukuyama, Yukio; Mukai, Hitoshi
Abstract The Tohoku earthquake of 11 March 2011, with moment magnitude Mw = 9.0, and subsequent tsunami caused catastrophic structural damage in east Japan. Using high‐frequency atmospheric monitoring data, we show that emissions of halocarbons, potent greenhouse gases and stratospheric ozone‐depleting substances, dramatically increased shortly after the earthquake and that annual emissions were significantly higher in 2011 than in other years. We estimate that the sum of earthquake‐related emissions of the six studied halocarbon species (CFC‐11, HCFC‐22, HCFC‐141b, HFC‐134a, HFC‐32, and SF6) was 6.6 (5.2–8.0) Gg, which is equivalent to ozone depletion potential‐weighted emissions of 1.3 (1.1–1.6) Gg with a global warming potential equivalent to 19.2 (15.8–22.5) Tg of carbon dioxide. These extraordinary halocarbon emissions are likely due to destruction of building components containing halocarbons, such as air conditioners, foam insulation, and electrical equipment.